FIXTURE DESIGN IN HOLE MACHINE AT PT. FLEXINDO PLASTIC KARAWANG - Setiyawan, Reza; Santosa, Aa; Oleh (Jurnal Mekanika dan Manufaktur, 2022)
The hole machine is a punching machine that is specially designed to punch holes in plastic bags, this machine is driven by a cylinder. Fixture is a tool that serves to direct one or more cutting tools in a position that is in accordance with the process of working on a product. After designing the fixture, the size of the fixture is 10mm thick, 900mm long, and 800mm wide. And the material used is multiplex, because this material has a smooth surface so it will not damage the texture of the plastic.